Association Between Endometritis and Endometrial Polyp: A Mendelian Randomization Study - Wei L; Zhao Y; Xu S; Zhang C (Dove Medical Press, 2023)
Longlong Wei,1,2 Yan Zhao,2 Siyue Xu,2 Cuilian Zhang1,2 1Department of Reproductive Medicine Center, People's Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of China; 2Department of Reproductive Medicine Center, Henan Provincial People's Hospital, Zhengzhou, Henan, People's Republic of ChinaCorrespondence: Cuilian Zhang, Email zclian@zzu.edu.cnBackground: Endometrial polyps (EPs) are one of the most common intrauterine benign tumors, and are an important cause of uterine bleeding and female infertility. Previous studies have suggested that endometritis may contribute to the onset of EPs. This study aims to reveal the causal effect of endometritis on EPs by a two-sample Mendelian randomization (MR) study.Methods: Utilizing summarized statistics from genome-wide association studies (GWAS) in the European population, we conducted a Mendelian randomization study. In order to select suitable instrumental variables (IVs) that were significantly related to the exposures, a number of quality control approaches were used. For endometritis, 2144 cases and 111,858 controls were included, while for EPs, 2252 cases and 460,758 controls. Utilizing the inverse variance weighted (IVW) as the primary analysis, the data were subjected to a two-sample MR analysis, and the weighted median (WM) technique and MR-Egger regression were carried out additionally. The sensitivity analysis revealed neither heterogeneity nor horizontal pleiotropy.Results: Four independent single nucleotide polymorphisms (SNPs) from endometritis GWAS as IVs were selected. The IVW data did not agree to a causal association between endometritis and EPs (β=1.11e-04, standard error [SE] =4.88e-04, P = 0.82). Directional pleiotropy did not affect the outcome, according to the MR-Egger regression (intercept = 0.09, P = 0.10); Additionally, it showed no causation association between endometritis and EPs (β= − 3.28e-03, SE = 3.54e-03, P = 0.45). Similar results were obtained using the weighted-median method (β=8.56e-05, SE=5.97e-04, P = 0.89). No proof of heterogeneity and horizontal pleiotropy between IV estimates was discovered.Conclusion: In conclusion, by large scale genetic data, the results of this MR analysis provided suggestive evidence that the presence of endometritis is not associated with higher EPs risk.Keywords: two-sample Mendelian randomization, GWAS, endometritis, endometrial polyp